Metadiscourse in Applied Linguistics Research Articles: A Cross-Sectional Survey - Kuhi, Davud; Yavari, Mahin; Azar, Ali Sorayyaei (Richtmann Publishing, 2012)
The literature on the generic features of academic discourse has revealed that the communicative purposes ofdifferent sections of research reports (e.g. research articles) affect the degree of tentativeness, flexibility, and authorialengagement realized by various linguistic resources. Following this assumption, a corpus of 32 research articles in the field ofapplied linguistics were analyzed in order to find out both the cross-sectional (i.e. Introduction-Methodology-Results-Discussion/Conclusion) variations in the use of metadiscourse – as a key tool for establishing interpersonal relationships inacademic writing. Hyland’s (2005) taxonomy of metadiscourse was applied to analyze the data set. The findings of the studyrevealed that the authors utilized interpersonal features differently in the four rhetorical atmospheres of their texts. Writerstended to employ high frequency of interactive metadiscourse resources in the introduction section of their articles, while in thediscussion/conclusion section writers utilized more interactional resources. The findings clearly indicate that the differences inthe discoursal functions of different sections of a research report play a significant role in writers’ fashioning of interactive andinteractional features. The results of this study can be drawn on in academic writing courses for research students and novicewriters in order to facilitate their achievement in academic writing.